ROCCS set to break down the processing barrier. Issue 1 (January 2016) - Price, Simon
Abstract : A look back at the forecasts made by composite industry analysts for carbon fiber demand show that the current take up has fallen far short of expectations. In defending their forecasts the analysts will point to unforeseen macroeconomic factors but the question needs to be asked: "is one of the biggest restraints caused by the composite industry itself?"